THE TRANSFORMATION OF ISLAMIC EDUCATION AND THE GLOBAL FUTURE CHALLENGES OF ISLAMIC HIGHER EDUCATION IN INDONESIA - Marjuni, Marjuni (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This study aims to reveal the global challenges encountered by Islamic higher education in Indonesia and the transformation of Islamic Education in the era of globalization, namely the digital era and the industrial revolution 4.0. This research employs a qualitative method using a sociological approach. The data were obtained through interviews with lecturers and practitioners of Islamic Education at the Faculty of Education and Teacher Training at Alauddin State Islamic University of Makassar (UIN Alauddin Makassar). The findings of this study revealed that Islamic Education is urgently needed by the community in the midst of advances in science and technology. Islamic Education is viewed as an educational paradigm that can prevent modern society from being trapped in a value shock or culture shock. Transforming Islamic Education's principles and values is critical in countering the current and future global challenges. This study gives insights on the development of Islamic knowledge and the development of community-based human resources, particularly on the integration of Islamic teachings into general studies. Abstrak: Penelitian ini bertujuan untuk mengungkap tantangan global yang dihadapi perguruan tinggi Islam di Indonesia dan transformasi Pendidikan Islam di era globalisasi yaitu era digital dan revolusi industri 4.0. Penelitian ini menggunakan metode kualitatif dengan pendekatan sosiologis. Data diperoleh melalui wawancara dengan dosen dan praktisi Pendidikan Agama Islam pada Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Negeri Alauddin Makassar (UIN Alauddin Makassar). Temuan penelitian ini mengungkapkan bahwa Pendidikan Agama Islam sangat dibutuhkan oleh masyarakat di tengah kemajuan ilmu pengetahuan dan teknologi. Pendidikan Islam dipandang sebagai paradigma pendidikan yang dapat menghindarkan masyarakat modern agar tidak terjebak dalam kejutan nilai (value shock) atau kejutan budaya (culture shock). Transformasi prinsip-prinsip dan nilai-nilai Pendidikan Islam sangat penting dalam menghadapi tantangan global saat ini dan masa depan. Penelitian ini menambah wawasan mengenai perkembangan ilmu keislaman dan perkembangan sumber daya manusia yang berbasis masyarakat khususnya dalam integrasi ajaran Islam ke dalam studi umum.